2013
DOI: 10.1371/journal.pone.0066985
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Killing Effects against Mycobacterium tuberculosis by Alveolar Macrophages from Young and Aged Rhesus Macaques

Abstract: Non-human primates, notably rhesus macaques (Macaca mulatta, RM), provide a robust experimental model to investigate the immune response to and effective control of Mycobacterium tuberculosis infections. Changes in the function of immune cells and immunosenescence may contribute to the increased susceptibility of the elderly to tuberculosis. The goal of this study was to examine the impact of age on M. tuberculosis host-pathogen interactions following infection of primary alveolar macrophages derived from youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…While these data suggest that investigators should not extrapolate upon mouse data too heavily, other studies have shown that certain aspects of immune control are conserved. We showed that autophagic killing of M. tuberculosis occurs in alveolar macrophages from rhesus macaques, recapitulating our previous experiments performed using murine BMDMs (36, 52). In addition, we used alveolar macrophages to ask whether this autophagic killing was impaired upon aging, since this pathway is thought to be diminished with age.…”
Section: Model Systems Overviewsupporting
confidence: 88%
“…While these data suggest that investigators should not extrapolate upon mouse data too heavily, other studies have shown that certain aspects of immune control are conserved. We showed that autophagic killing of M. tuberculosis occurs in alveolar macrophages from rhesus macaques, recapitulating our previous experiments performed using murine BMDMs (36, 52). In addition, we used alveolar macrophages to ask whether this autophagic killing was impaired upon aging, since this pathway is thought to be diminished with age.…”
Section: Model Systems Overviewsupporting
confidence: 88%
“…For semiquantitative analysis, at least 100 cells were response in myelocytic cells (30). However, our results provide an explanation for the observation that clinical isolates of M. tuberculosis manipulate autophagy for their survival (40) and mirror those seen in M. tuberculosis infection of human primary dendritic cells (41), human type II alveolar epithelial cells (42), and some primary alveolar macrophages from adult macaques (43). Consistent with our observations, in Listeria-infected macrophages, bacteria are localized to both the cytosol and LC3 + compartments in which bacteria grow (44), and long-term infection of macrophages with M. bovis BCG also leads to growth of the bacteria in LC3 + compartments (45).…”
Section: Methodsmentioning
confidence: 70%
“…Many other studies on bacterial infection have focussed on how changes in the immune system during ageing can influence infection. However, contradicting evidence regarding immune-senescence indicates the presence of other confounding factors (Esposito and Pennington, 1983; Cooper et al ., 1995; Pacheco et al ., 2013), which may decide the final outcome of infection in the aged.…”
Section: Discussionmentioning
confidence: 99%